Conquering pyoderma gangrenosum: exploring non-steroidal treatment options - Chaurasia, Sharad K.; Bhattacharya, Ipshita; Dhaka, Kanchan; Gupta, Piyush; Dsouza, Paschal (International Journal of Research in Dermatology, 2023)
Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis frequently related to chronic inflammatory bowel disease (IBD) and often associated with exacerbation of intestinal disease and/or loss of treatment efficacy. The mainstay of treatment is long-term immunosuppression, often with high doses of corticosteroids or low doses of ciclosporin. PG has been reported to respond to TNF alpha inhibitors. We report a patient of recalcitrant PG who responded very well to treatment with golimumab. A 61-year-old known case of PG since 4 years, who also had history of hypertension, pulmonary TB (treated), had been treated with dapsone, thalidomide, colchicine and corticosteroids in the past with partial response and frequent relapses. In February 2021, the patient while being on low-dose oral corticosteroids and colchicine, presented with large painful ulcer over back of his right thigh, which rapidly worsened. In agreement with the pulmonologist, the patient was started on Injection golimumab in addition to intravenous dexamethasone with slow tapering of steroid dosage following the improvement of the cutaneous lesion. Patient reported a near-total resolution of lesion after two doses. He is maintaining well with golimumab. PG can be poorly responsive despite adequate treatment with conventional modalities. High dose steroid therapy with all expected iatrogenic complications and treatment with cyclosporine in such an elderly patient with hypertension and history of tuberculosis seemed to be inappropriate. For all these reasons, a treatment with the TNF alpha inhibitor golimumab, appeared to be the most reasonable therapeutic choice for a patient.